The Implementation of Patient-Centered Collaborative Care Training Concept to Increase Inpatient Unit Nurse Performances of X Hospital - Yeyen Gustina Irawan (Universitas Muhammadiyah Yogyakarta, 2019)
The implementation of best Patient-Centered Collaborative Care training concept becomes one of the important aspects of providing health services in a hospital. The improvement of health services conducted bt the hospital is aimed to support healing and recovery with the full attention of patient comfort. This study used Mixed Method Research or a combination of quantitative and qualitative approaches os Sequential Explanatory, and qualitative data analysis in the second stage, to support the quantitative research finding which is done in the first stage. This study used One Group Pre – Test – Post – Test Design without Control, is a way of performing one pretest- before treatment (treatment/training) and afterward measuring again (post-test) without giving a control treatment. There are 96 respondents with one year of minimum work period in X Hospital. The respondent's observations are included gender, educational background, work period, status, children, residence and the workplace. The result of this study shows that the highest level of nurse’s knowledge is influenced by the age, work experience, educational background, and motivation of self-development. Statistically, there are no signification differences, but from training appreciation, a nurse is unrealized that there is the influence of PCC implementation at the Surgical and Intern Ward Inpatient Unit X Hospital and supported by nurse’s performances. Good knowledge of PCC concept proved to have an effect on PCC implementation inpatient Surgery and Interna Ward X Hospital supported by the improvement of nurse performance in inpatient room.